1998
DOI: 10.1093/jac/41.2.277
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization of Burkholderia cepacia to antibiotics by cationic drugs

Abstract: Chlorpromazine and prochlorperazine have previously been shown to enhance the susceptibility of Burkholderia cepacia to aminoglycosides. To screen other non-antibiotic drugs containing similar amine (-N-CH3) groups, we examined a range of such agents that are in current clinical use for the treatment of non-infectious diseases, in combination with antibiotics that are ineffective against B. cepacia. At a concentration of 0.2 mM, theobromine, theophylline, trifluoperazine, fluophenazine and coumarin-152 signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…The antibiotic potentiator chlorpromazine reduced the MIC of amikacin (200 to 100 mg/L), tobramycin (150 to 50 mg/L) and azithromycin (50 to 15 mg/L) at a concentration of 0.2 mM; the same concentration of prochlorperazine produced slightly greater reductions in antibiotic MIC (amikacin to 20, tobramycin to 20 and azithromycin to 10 mg/L). These reductions were consistent with previous data obtained for " B. cepacia " strain ATCC 13945 [13] which is a B. cenocepacia IIIA strain, but not from the ET12 lineage (see http://pubmlst.org/bcc. As theophylline was not found to alter the susceptibility of strain J2315, chlorpromazine in combination with amikacin was selected as the optimal potentiator-antibiotic combination to examine from the B. cenocepacia global gene expression perspective because it had a good additive effect, did not present solubility problems in growth medium as seen with prochlorperazine, and allowed reproducible growth curves to be obtained for strain J2315.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The antibiotic potentiator chlorpromazine reduced the MIC of amikacin (200 to 100 mg/L), tobramycin (150 to 50 mg/L) and azithromycin (50 to 15 mg/L) at a concentration of 0.2 mM; the same concentration of prochlorperazine produced slightly greater reductions in antibiotic MIC (amikacin to 20, tobramycin to 20 and azithromycin to 10 mg/L). These reductions were consistent with previous data obtained for " B. cepacia " strain ATCC 13945 [13] which is a B. cenocepacia IIIA strain, but not from the ET12 lineage (see http://pubmlst.org/bcc. As theophylline was not found to alter the susceptibility of strain J2315, chlorpromazine in combination with amikacin was selected as the optimal potentiator-antibiotic combination to examine from the B. cenocepacia global gene expression perspective because it had a good additive effect, did not present solubility problems in growth medium as seen with prochlorperazine, and allowed reproducible growth curves to be obtained for strain J2315.…”
Section: Resultssupporting
confidence: 92%
“…The molecular mechanisms behind the evolution of spontaneous antimicrobial resistance in B. cenocepacia are not known and how the multiple resistance pathways function on a global scale to allow B. cenocepacia to survive antibiotic therapy is poorly understood. Cationic drugs such as chlorpromazine and theophylline have been shown to reduce the minimal inhibition concentration (MIC) of certain antibiotics that are otherwise ineffective against Bcc bacteria [13] and a more complete understanding of how these non-antibiotic drugs act may also provide novel therapies.…”
Section: Introductionmentioning
confidence: 99%
“…Although cationic peptides and antibiotics appear to be unable to kill Bcc organisms, they may enhance the antimicrobial activity of other antibiotics (37,38), providing physicians with a broader spectrum of therapeutic options for Bcc infections.…”
mentioning
confidence: 99%
“…Thus, it is more probable that the synergy between drugs results from the ability of promethazine either to facilitate the influx of drugs through the cell membrane or to inhibit the efflux pumps of various bacteria [35], including E. coli [36,37]. The finding that penicillin G, in contrast to ampicillin, does not pass the outer membrane of Gram-negative bacteria [16] as well as the fact that many cationic compounds [38,39] such as phenothiazines [3,10,11] have a direct action on membrane permeability in Gram-negative bacteria by directly interacting with LPS [40,41], which leads to disruption of the interaction site and to the enhanced uptake of molecules across the outer membrane, suggest that promethazine may directly facilitate the penetration of penicillin G into cells. Expression of efflux pumps is generally observed in clinical bacteria [42] and is associated with reduced drug accumulation, which causes increased resistance to antibiotics in bacteria [14].…”
Section: Discussionmentioning
confidence: 99%
“…During the past decades, it has been found that tricyclic neuroleptics, especially phenothiazines such as promethazine, employed for treatment of psychosis exhibit direct antimicrobial activity against various microorganisms [1,2] as well as enhancing the activity of conventional antibiotics [3][4][5]. The mechanisms by which phenothiazines may enhance the activity of conventional antibiotics have been postulated to involve at least three alternative mechanisms: (i) phenothiazines may interact with an antibiotic forming a charge-transfer complex (CTC) [6], which has increased antimicrobial activity compared with a single drug; (ii) alternatively, phenothiazines may alter the transport function of the cell membrane by inhibiting the bacterial efflux pumps, resulting in accumulation of antibiotics in the cells [7][8][9]; and (iii) cationic phenothiazines may have a direct action on the permeability of the cell membrane [3,10,11], thus facilitating the influx of antibiotics.…”
Section: Introductionmentioning
confidence: 99%